TRENDS IN MILLETS PRODUCTION, CONSUMPTION AND EXPORT FROM INDIA - O P Singh (The Journal of Research ANGRAU, 2024)
In the year 2021, total area under millets cultivation in India was 9.76 million hectares accounting for 31.55 percent of world’s total area.Total production of millets in India was 13.21 million tonnes in 2021 contributing about 43.90 percent to world’s total millets production. The objective of this study was to analyse the growth performance of millets production in India and world, and exports of millets (quantity and value) from India. The study was based on secondarydata and the analysis was carried out using compound growth trend and decomposition analysis. In India, millets area and production reduced during 1966-67 to 2019-20, whereas, per hectare yield increased with compound growth rate of 1.08 percent per annum. Decomposition analysis suggested that yield was negatively affecting the overall growth in production of finger millet, minor millet and sorghum, whereas, it was positive for pearl millet. Total export of millets from India was 27.42 million USD in 2021 and it was growing with a compound growth rate of 15.67 percent per annum during 1981-2021.The index value of revealed comparative advantage, revealed symmetric comparative advantage, revealed competitive advantage and trade specification coefficient index suggested that India has comparative advantage and competitiveness in export of millets to different parts of the world.